Factors Influencing Aggressiveness among Adolescent School Children - Thapa, Sneha (Journal of Durgalaxmi, 2025)
Adolescents are those who goes through behavior problems and aggressive behavior is one of the major behavioral problems. Aggression is a behaviour that is intended to hurt or injure another either physically (hitting, slapping, kicking, bullying, etc.) or verbally (insulting, rude, sarcasms, arguments, etc.) or through their strong emotions to harm another (anger) or having negative behaviour to threat another (hostility).Kind of family, currently living status, parent-child relationship, safety at school, truancy, number of close friends and peer relationship are found to be the factors of aggression among adolescents. A cross-sectional descriptive study will be conducted to assess factors affecting aggressiveness among adolescents. The study was conducted in Nava Arunima Secondary School among the adolescents studying in grade 8 to 10. Non probability total enumerative sampling technique was adopted to select the sample. Sample size was 126. Self-administered questionnaire technique was used to collect the data using standard tool of Buss-Perry aggression scale, 1992 and self-developed structured questionnaire. Descriptive analysis like frequency, percentage, mean, standard deviation, and inferential statistics like chi-square test was done. SPSS version 20 was used to analyze the data. The finding of the study reveals that majority of respondents 74.6% had aggression and 25.4% had no aggression and there is significant association between peer relationship and aggression (p=0.017).The majority of respondents had aggression and there is significant association between peer relationship and aggression. With respect to finding, it is necessary to conduct counseling programme for aggression management by school management.